2021
DOI: 10.1002/adfm.202103408
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining Reversible, High Contrast Electrochromism, Electrofluorochromism, and Photochromism in an Aqueous Hydrogel Device Using Chromogenic Thiazolothiazoles

Abstract: There have been an increasing number of materials developed that show multifunctional chromogenic properties (such as electrochromism, electrofluorochromism, or photochromism), but to date, few materials have shown all three properties. Materials that are electrochemically and optically active are attractive for a diverse set of applications that include smart‐windows, lighting, sensing, energy production, and conservation. This is especially attractive for building developers interested in adaptive or environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 46 publications
(75 reference statements)
1
39
0
Order By: Relevance
“…These results indicated that the introduction of borate had no negative effects on the intrinsic electrochromic performance of the ECD. The P­(GMA 2 -AAm 8 )-borate hydrogel electrolyte was compared with reported hydrogel systems for ECDs , and their properties are summarized in Table S2. Our hydrogel electrolyte and the flexible ECD showed better performance than reported works in terms of mechanical properties, self-healing performance, and electrochromic performance.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the introduction of borate had no negative effects on the intrinsic electrochromic performance of the ECD. The P­(GMA 2 -AAm 8 )-borate hydrogel electrolyte was compared with reported hydrogel systems for ECDs , and their properties are summarized in Table S2. Our hydrogel electrolyte and the flexible ECD showed better performance than reported works in terms of mechanical properties, self-healing performance, and electrochromic performance.…”
Section: Resultsmentioning
confidence: 99%
“…Devices using water-soluble, chromogenic thiazolo(5,4-d) thiazole (TTz) dyes were developed by a research group headed by Michael Walter [ 35 ]. They synthesized viologens from TTz and these were later studied in PVA/borax hydrogel devices from which the ease-to-assemble and high oxidative stability in the air were highlighted.…”
Section: Supramolecular Structures With Photoresponsive Unitsmentioning
confidence: 99%
“…Recently, considerable attention has been paid to CMPs linked by TzTz that could endow them with exceptional optoelectronic properties. 49–51 Nevertheless, the CMPs linked by the electron-deficient TzTz have been relatively underexploited for visible light photocatalysis. There were sporadic studies that revealed their great potential in H 2 evolution, 52 CO 2 reduction, 53 and dye degradation.…”
Section: Introductionmentioning
confidence: 99%